Optimasi Pemanfaatan Sampah Kertas Layak Jual di Kampus Universitas Andalas, Limau Manis Padang - Yenni Ruslinda; Anita Pra Ramadhani; Hendra Gunawan (Jurnal Serambi Engineering, 2024)
The increasing demand for paper products over time has led to a corresponding increase in the amount of paper waste generated. Andalas University Campus endorses the recycling concept through the establishment of an Integrated Waste Management Center (PPST), which encompasses the Andalas Enviro Waste Bank (BSEA). This center is designed to oversee the management of dry waste that is suitable for sale, with the proceeds from such sales being directed to third parties. This study examines the optimization of paper waste utilization at the Andalas University Campus in Limau Manis, Padang. The study referenced data on the generation, composition, and recycling potential of paper waste from the Unand campus, as well as existing conditions of paper waste management at each source, obtained through the distribution of questionnaires and interviews. The results of the calculations demonstrate that the quantity of paper waste suitable for sale on the Unand campus is 779.82 kg/day. The BSEA is responsible for the collection of this waste through the waste bank system. The study was conducted by creating three scenarios for the management of paper waste: (I) direct sales of paper waste without processing; (II) processing of cardboard waste into egg containers and other types of paper waste into recycled paper; and (III) processing of HVS paper waste and selling other paper waste. The results of the assessment, conducted using incremental IRR analysis and scoring methods, indicated that scenario III was the optimal management scenario for optimizing the utilization of marketable paper waste at the Andalas University Limau Manis Campus from a technical and financial perspective.